1995
DOI: 10.1007/bf00010482
|View full text |Cite
|
Sign up to set email alerts
|

Root length dynamics in agroforestry with Gliricidia sepium as compared to sole cropping in the semi-deciduous rainforest zone of West Africa

Abstract: Tree root systems may improve soil fertility through carbon inputs, uptake of leachable nutrients and maintenance of soil biomass, but can at the same time reduce crop yields by competition for water and nutrients. Quantitative information about the positive and negative effects of tree roots and their changes in space and time are necessary for the optimization of agroforestry associations. An alley cropping experiment was layed out as a randomized complete block design on a Plinthic Lixisol/Ferralic Cambisol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(19 citation statements)
references
References 21 publications
(26 reference statements)
3
15
0
1
Order By: Relevance
“…On the other hand studies at Makoka in Malawi observed that gliricidia has very deep rooting systems (>3 m), with < 15% at the top 0-20 cm soil and 79% to 63% of the roots below the effective rooting zone of maize (0-30 cm depth), indicating a differential rooting pattern between trees and crops and low potential for competition. A similar study in Cô te d'Ivoire had also suggested that gliricidia have few surficial roots and minimally compete with associated crops (Schroth and Zech 1995). These studies confirmed that gliricidia rooting patterns are different from those of maize.…”
Section: Treesmentioning
confidence: 53%
“…On the other hand studies at Makoka in Malawi observed that gliricidia has very deep rooting systems (>3 m), with < 15% at the top 0-20 cm soil and 79% to 63% of the roots below the effective rooting zone of maize (0-30 cm depth), indicating a differential rooting pattern between trees and crops and low potential for competition. A similar study in Cô te d'Ivoire had also suggested that gliricidia have few surficial roots and minimally compete with associated crops (Schroth and Zech 1995). These studies confirmed that gliricidia rooting patterns are different from those of maize.…”
Section: Treesmentioning
confidence: 53%
“…Less depletion of soil water in the crop rooting zone associated with reduction in root length density in pruned plots of P. juliflora in a semi-arid region of north-east Nigeria has been previously reported ( Jones et al, 1998). A reduction of root density following pruning has also been found in A. saligna (Peter & Lehmann, 2000), Sesbania sesban and L. leucocephala (Fownes & Andersson, 1991), and G. sepium (Schroth & Zech, 1995). Many more species maintain a balanced shoot-to-root ratio and grow a large number of superficial roots when pruned, including Cassia siamea and Calliandra calothyrsus Meissn.…”
Section: Discussionmentioning
confidence: 89%
“…In the nature, the latter may occur if the rhizospheres of the two species overlap. Given the very high fine root density of both trees and crops in some agroforestry systems (Dossa et al 2008;Muñoz and Beer 2001;Schroth and Zech 1995) overlap of rhizospheres and, consequently, N transfer via the exudate pathway is likely. The formation of CMN may require that both plant species form symbiosis with the same fungal species because anastomoses, functional connections between hyphae, mostly occur between fungi of same species (Giovannetti et al 2006).…”
Section: Introductionmentioning
confidence: 99%